Culprit-plaque morphology and residual SYNTAX score for predicting cardiovascular events in acute myocardial infarction: an optical coherence tomography study. (14th October 2021) - Wang, Y; Zhao, X X; Zhou, P; Liu, C; Li, J N; Zhou, J Y; Chen, R Z; Chen, Y; Song, L; Zhao, H J; Yan, H B
Abstract: Background: Previous studies reported that different culprit-plaque morphologies [plaque rupture (PR) and plaque erosion (PE) identified by optical coherence tomography (OCT)] might influence clinical outcomes in patients with acute myocardial infarction (AMI). Moreover, residual SYNTAX score (rSS) was proved to be related to worse prognosis. Purpose: This study aimed to investigate the prognostic implication of culprit-plaque morphologies and rSS for major adverse cardiac events (MACE) in patients with ST-segment elevation myocardial infarction (STEMI). Methods: A total of 369 STEMI patients undergoing preintervention optical coherence tomography examination were included and divided into 4 groups based on PR and rSS: PE/low-rSS (n=92), PE/high-rSS (n=82), PR/low-rSS (n=80) and PR/high-rSS (n=115). The rSS was determined as the SYNTAX score remaining after completion of planned PCI. MACE was defined as the composite of all-cause death, recurrence of myocardial infarction (MI), stroke and unplanned revascularization of any coronary artery. K-M survival analysis and cox regression with adjustments for multiple covariates was used for outcome analysis. Results: During a mean follow-up of 2.2 years, MACE occurred in 58 (15.7%) patients: 7.6% (7 patients) among patients with PE/low-rSS, 13.4% (11 patients) among patients with PE/high-rSS, 6.3% (5 patients) among patients with PR/low-rSS and 25.2% (29 patients) among patients with PR/high-rSS (p=0.001). In fully adjusted analyses, patients with PR/high-rSS presented higher MACE risk than patients with PE/low-rSS (HR: 3.17, 95% CI: 1.37–7.33, P=0.007). Conclusion: In STEMI patients, patients with PR/high-rSS had worse prognosis, indicating culprit-plaque morphology and residual atherosclerosis burden should be taken into account in risk stratification and management of patients with STEMI. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Chinese Academy of Medical Sciences Innovation Fund for Medical Sciences